Unveiling the Frontiers of Synthetic Biology in Brazil: Pioneering the National Synthetic Biology Network - Santos, Leandro V.; Maklouf, Giovanna R.; do Nascimento, Cibele Z. S.; Lins, Milca R. C. R.; Rezende, Juliana C.; Rojas, Cristian A.; Sampaio, Yala; Kadri, Nájua K. El; Kundlatsch, Guilherme E. [UNESP]; Simão, Rita C. G.; Rech, Elibio L.; Silva, Luiziana F.; et al. (American Chemical Society (ACS), 2025)
In the past two decades, synthetic biology has emerged as a transformative field at the frontier of innovation, evolving from fundamental technological advancements to the commercialization of innovative products. The field is providing breakthrough innovations to address societal challenges and has become a key technology for the sustainable development of global economies. This ongoing revolution represents an opportunity for countries to mitigate the damage caused by decades of reckless use of global resources. In Brazil, a growing community is harnessing this potential, driven by a shared vision and collaborative efforts. The establishment of the Brazilian Synthetic Biology Network marks a pivotal moment in bringing together diverse research groups and fostering interdisciplinary partnerships. By leveraging the nation's rich biodiversity, scientific expertise, and bioproduction capacity, Brazil is well-positioned to lead advancements in sustainable solutions based on synthetic biology. To realize its potential, the country needs a strong and well-connected scientific community, long-term investments in infrastructure, and the development of domestic infrastructure for supplying critical materials, reagents, and core services that support synthetic biology research and innovation. The Brazilian Synthetic Biology Network represents a significant milestone in advancing Brazil's biotechnological capabilities. While the Brazilian potential is clear for the Network members, the scientific and regulatory scenario in Brazil is poorly known by the international community. This review discusses key components of the synthetic biology ecosystem in Brazil and highlights the limitations that hinder the country's technological development.